2012
DOI: 10.5194/acp-12-2777-2012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic multi-layer model of gas-particle interactions in aerosols and clouds (KM-GAP): linking condensation, evaporation and chemical reactions of organics, oxidants and water

Abstract: Abstract. We present a novel kinetic multi-layer model for gas-particle interactions in aerosols and clouds (KM-GAP) that treats explicitly all steps of mass transport and chemical reaction of semi-volatile species partitioning between gas phase, particle surface and particle bulk. KM-GAP is based on the PRA model framework (Pöschl-RudichAmmann, 2007), and it includes gas phase diffusion, reversible adsorption, surface reactions, bulk diffusion and reaction, as well as condensation, evaporation and heat transf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
258
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(278 citation statements)
references
References 89 publications
4
258
2
1
Order By: Relevance
“…Particle size has been discussed primarily in the context of accumulation mode particles greater than 100 nm in diameter (Roldin et al, 2014;Shiraiwa et al, 2013;Vesterinen et al, 2007). The Vesterinen study did report aerosol yield functions from simulations starting with 20 nm diameter seed particles, and the results suggested that particle-phase chemistry could enhance growth rates under atmospherically relevant conditions.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Particle size has been discussed primarily in the context of accumulation mode particles greater than 100 nm in diameter (Roldin et al, 2014;Shiraiwa et al, 2013;Vesterinen et al, 2007). The Vesterinen study did report aerosol yield functions from simulations starting with 20 nm diameter seed particles, and the results suggested that particle-phase chemistry could enhance growth rates under atmospherically relevant conditions.…”
Section: Introductionmentioning
confidence: 91%
“…for constraining aerosol formation models. Future modeling of size-dependent molecular composition should include physico-chemical parameters such as diffusion, phase separation, and reaction reversibility (Liu et al, 2014;Mai et al, 2015;Riipinen et al, 2012;Shiraiwa et al, 2012;Song et al, 2015;Trump and Donahue, 2014;Zaveri et al, 2014) that may influence the contribution of particlephase chemistry to nanoparticle growth.…”
Section: Comparison To Recent Experimental Measurements and Atmosphermentioning
confidence: 99%
“…The characteristic timescale to reach equilibrium partitioning can be estimated using the kinetic multi-layer model of gas-particle interactions (KM-GAP) 35 coupled with AIOMFAC. KM-GAP represents the particle phase with multiple compartments and layers, including a surface sorption layer and a number of bulk layers and treats gas-phase diffusion, reversible adsorption, and bulk diffusion explicitly (see Fig.…”
Section: Equilibration Timescale Of Soa Partitioningmentioning
confidence: 99%
“…The "kinetic multi-layer model of gas-particle interactions in aerosol and clouds" (KM-GAP) (Shiraiwa et al, 2012), based on coupled differential equations;…”
Section: S O'meara Et Al: the Rate Of Equilibration Of Viscous Aeromentioning
confidence: 99%